Traces of Dance in Basic Education in the 1970s: SECE-PE and the Recife Ballet Company Agreement (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This educational/dance study examines fragments of the agreement between SECE-PE and the Recife Ballet Company in the 1970s, a period under the Military Dictatorship marked by repression and the emergence of cultural policies. The Recife Ballet Company promoted national circulation, international exchange, and pedagogical projects aimed at bringing dance closer to students and teachers in public schools. Although the agreement fostered artistic dissemination, it revealed structural and conceptual limitations, leaning more toward a performance logic than curricular transformation. In this context, dance education oscillated between institutionalization, creation, and expression.
Keywords: dance; Recife; basic education; 1970s; Recife Ballet Company